“Sicherungsverwahrung” (preventive detention) in Germany under the scrutiny of the ECHR - Mühlenbrock, Hannes (Riga Graduate School of Law, 2020)
The societal challenge how to deal with offenders deemed habitually dangerous, requires to balance needs for security of the general public with the human rights of the potential extreme dangerous offender. The prediction of future heavy crimes can never be precise. Hence, all measures infringing the rights of individuals deemed dangerous are very problematic from a human rights perspective. Germany uses “Sicherungsverwahrung” (preventive detention) to handle this challenge. The concept basically meant that after their prison-sentence, offenders deemed dangerous were kept in prison like conditions until they were not deemed dangerous anymore. The European Court of Human Rights (ECtHR) interfered after such measures were prolonged and ordered retrospectively. The thesis shows that also the non-retrospective forms of preventive detention were problematic under the European Convention on Human Rights, because preventive detention did hardly differentiate from a penalty albeit classified as purely preventive in Germany. The ECtHR triggered reforms of preventive detention that started a development to more human rights conformity, but, as argued in the thesis, the ECtHR accepted new forms of preventive detention that still violate the Convention. Consequently, Germany still needs to solve the challenge of dealing with offenders deemed dangerous in accordance with human rights.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International private law and international procedural law; Preventive detention; Human rights